1987
DOI: 10.1172/jci113166
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fetal adrenalectomy on catecholamine release and physiologic adaptation at birth in sheep.

Abstract: Plasma catecholamine levels increase dramatically at birth. To determine the contribution of adrenal catecholamine secretion to the surge in catecholamines at birth and the role in newborn adaptation, we performed surgical adrenalectomy or sham operation on near-term ovine fetuses. After recovery in utero, the animals were delivered and supported by mechanical ventilation. Plasma catecholamine levels, heart rate, blood pressure, cardiac output, pulmonary function, surfactant secretion, and release of free fatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
0
2

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 35 publications
(29 reference statements)
3
47
0
2
Order By: Relevance
“…As compared with babies exposed to a trial of labor, babies delivered by elective cesarean section (even near term) show (a) an increased risk of respiratory morbidity (Cohen & Carson, 1985;Zanardo et al, 2004); (b) a fivefold increase in the likelihood of persistent pulmonary hypertension (Levine, Ghai, Barton, & Strom, 2001); (c) lower dynamic lung compliance (Faxelius, Hagnevik, Lagercrantz, Lundell, & Irestedt, 1983) and higher functional residual capacity, possibly as an adaptation to elevated lung water content (Hagnevik, Lagercrantz, & Sjoqvist, 1991); (d) increased incidence of postpartum respiratory distress (Irestedt, Lagercrantz, & Belfrage, 1984); (e) decreased protection from oxidative stress (Buhimschi, Buhimschi, Pupkin, & Weiner, 2003); and (f) delayed neurodevelopmental status (Otamiri, Berg, Ledin, Leijon, & Lagercrantz, 1991;Otamiri, Berg, Ledin, Leijon, & Nilsson, 1990). Animal studies of labor's effects on the fetus and newborn, conducted almost exclusively in the precocial sheep fetus, have revealed important roles of birth-related catecholamines, including stimulating lung liquid absorption (reviewed by Barker & Olver, 2002), sustaining metabolic and cardiac homeostasis (Padbury et al, 1987), and providing protection from hypoxia (C. T. Jones, 1980). Labor-induced catecholamine release may provide an important mechanism underlying the neonate's process of adapting to extrauterine conditions and the recruitment of vital postnatal behaviors (Ronca, Abel, & Alberts, 1996).…”
mentioning
confidence: 99%
“…As compared with babies exposed to a trial of labor, babies delivered by elective cesarean section (even near term) show (a) an increased risk of respiratory morbidity (Cohen & Carson, 1985;Zanardo et al, 2004); (b) a fivefold increase in the likelihood of persistent pulmonary hypertension (Levine, Ghai, Barton, & Strom, 2001); (c) lower dynamic lung compliance (Faxelius, Hagnevik, Lagercrantz, Lundell, & Irestedt, 1983) and higher functional residual capacity, possibly as an adaptation to elevated lung water content (Hagnevik, Lagercrantz, & Sjoqvist, 1991); (d) increased incidence of postpartum respiratory distress (Irestedt, Lagercrantz, & Belfrage, 1984); (e) decreased protection from oxidative stress (Buhimschi, Buhimschi, Pupkin, & Weiner, 2003); and (f) delayed neurodevelopmental status (Otamiri, Berg, Ledin, Leijon, & Lagercrantz, 1991;Otamiri, Berg, Ledin, Leijon, & Nilsson, 1990). Animal studies of labor's effects on the fetus and newborn, conducted almost exclusively in the precocial sheep fetus, have revealed important roles of birth-related catecholamines, including stimulating lung liquid absorption (reviewed by Barker & Olver, 2002), sustaining metabolic and cardiac homeostasis (Padbury et al, 1987), and providing protection from hypoxia (C. T. Jones, 1980). Labor-induced catecholamine release may provide an important mechanism underlying the neonate's process of adapting to extrauterine conditions and the recruitment of vital postnatal behaviors (Ronca, Abel, & Alberts, 1996).…”
mentioning
confidence: 99%
“…Birth in-duces a marked surge in catecholamine secretion (12). Increased catecholamines at delivery promote lung fluid reabsorption, surfactant release, and systemic circulatory adaptation (13,14). However, the effects on the pulmonary circulation are uncertain.…”
mentioning
confidence: 99%
“…I). The order of oxygen ventilation and isoproterenol to simulate the important catecholamine surge at birth (28,37), and volume loading. We measured left ventricular output, vascular pressures, and heart rate, and determined the individual and combined effects of each intervention on these variables.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that oxygen ventilation in utero creates a central circulatory pattern that is identical to the immediate postnatal circulation (3). In addition, the newborn left ventricle functions under significant fJ-adrenergic stimulation (8,37), which is essential to the increase in output at birth (28), and at higher filling pressures (6, 11) than before birth, so we performed the studies during isoproterenol infusion and volume loading in addition to oxygen ventilation. We found that oxygen ventilation and isoproterenol increased left ventricular output, but not volume infusion, and that the effect of oxygen ventilation far exceeded that of isoproterenol.…”
Section: Ascendingaortic Bloodjlow Mean Ascending Aortic Blood Flowmentioning
confidence: 99%
See 1 more Smart Citation